Clinical and Radiographic Features of the Autosomal Recessive form of Brachyolmia Caused by PAPSS2 Mutations. Issue 10 (26th July 2013) - Iida, Aritoshi; Simsek‐Kiper, Pelin Özlem; Mizumoto, Shuji; Hoshino, Touma; Elcioglu, Nursel; Horemuzova, Eva; Geiberger, Stefan; Yesil, Gozde; Kayserili, Hülya; Utine, Gülen Eda; Boduroglu, Koray; Watanabe, Shigehiko; et al.
<x xml:space="preserve">Abstract</x> Brachyolmia is a heterogeneous group of skeletal dysplasia characterized by generalized platyspondyly without significant long‐bone abnormalities. We revealed previously that an autosomal recessive form of brachyolmia is caused by mutations of PAPSS2 that encodes PAPS (3′‐phosphoadenosine 5′‐phosphosulfate) synthase 2. In this study, we identified nine types of mutations in 13 patients with brachyolmia from unrelated 10 families and characterized clinical and radiographic features of the PAPSS2‐brachyolmia. Enzyme assays for missense mutations confirmed that PAPSS2‐brachyolmia is caused by PAPSS2 deficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>